Pengembangan Edukasi Deteksi Dini Penyimpangan Perilaku Emosional Anak Prasekolah dengan Metode Blended Learning pada Guru PAUD - Khalida Ziah Sibualamu; Sri Resky Mustafa; Emmi Wahyuni (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of health education on the early detection of deviations in emotional behavior of preschool children using the blended learning method on the knowledge and skills of PAUD teachers in the Tamalanrea District, Makassar City. The research method used was a quasi-experimental pre-post with a control group design. The results showed a significant difference in the mean knowledge and skills scores between the intervention group and the control group (p<0.001). It is known that there is no significant difference in the mean pre-test scores of knowledge and skills between the two groups (p>0.05). However, the mean post-test scores showed a significant difference between the two groups, where the mean scores of knowledge and skills in the intervention group were higher than the control group (p<0.05). In conclusion, the blended learning method significantly affects the knowledge and skills of PAUD teachers regarding the early detection of emotional behavior problems. Keywords: Blended Learning, Early Detection, Knowledge, Emotional Behavior